Bangladesh development debates : perspectives from policy dialogues. - Centre for Policy Dialogue (Bangladesh) (Dhaka : Pathak Shamabesh Book : Centre for Policy Dialogue, 2001)
Contributed articles.
Includes index.
Keywords: South Asia -- Economic conditions